Hotel Chains: an Approach to their Origin and Evolution - Kowalczyk, Andrzej (Turyzm/Tourism, 2007)
In the world hotel industry the role of hotel chains is constantly growing. Although their origin relates to when the capitalist economy entered the stage of monopoly capitalism, their present development is connected to the phenomenon of globalization. The history of hotel chains can be divided into several stages whose beginnings and ends are marked by key events, essential not only for the hotel industry but also for the whole tourism economy.